American history : a visual encyclopedia - King, David C. (New York, NY : DK Publishing, 2019)
Offers a visual reference guide to American history, beginning with the first Native American cultures on the continent and ending in 2018.
"First American edition, 2003."
At head of title: DK Smithsonian.
Includes index.
Keywords: United States -- History -- Encyclopedias, Juvenile; United States -- History -- Pictorial works -- Encyclopedias; United States; Encyclopedias; History; Juvenile works